PENGARUH RASIO UDARA BAHAN BAKAR LPG TERHADAP FLAME TEMPERATURE DAN EFISIENSI TERMAL CROSS SECTION WATER TUBE BOILER - Apriani, Marsa; Susanti, Amalia; Has, Cresa Moneta; Tahdid; Manggala, Agus; Erlinawati; Zurohaina (Politeknik Negeri Sriwijaya, 2021)
Boiler is one of energy conversion machines. The boiler function is converting water into steam by utilizing the heat from the chemical reaction between fuel and oxygen in the air which is commonly known as the combustion reaction. The research purposes are to determine the effect of the LPG fuel air ratio on the flame temperature and thermal efficiency of cross section water tube boiler, and to determine the optimum fuel air ratio which produces the highest flame temperature and thermal efficiency. The air fuel ratio that use in this research are 29.16; 29.44; 29.71; 29.99; and 30,26. Based on the research, it is known that the fuel air ratio affects both of flame temperature and thermal efficiency of the cross section water tube boiler. On the range of air fuel ration 29.16 to 30.26, it is known that the greater the fuel air ratio, the higher the flame temperature and thermal efficiency The optimum air fuel ratio in this research is 29.99 which produces 680oC flame temperature and 58.85% on steady state saturated steam production, 7010C flame temperature and 59.71% thermal efficiency on non steady state saturated steam production, and 7040C flame temperature and 59.32% on superheated steam production.